ANALISIS PERAN KOPERASI SIMPAN PINJAM TERHADAP USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI KABUPATEN GORONTALO (STUDI PADA KSP “SURYA” UMG) - Nur Eng Mokodompit; Silvoni Rivai (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2021)
This research aims to: determine and analyze the role of Savings and Loan Cooperatives on Micro, Small and Medium Enterprises (MSMEs) in Gorontalo Regency (Study on KSP "SURYA" UMG). The research method uses a quantitative research approach with quantitative descriptive research. The result show that: 1) The role of the UMG Savings and Loan Cooperative "SURYA" provides enormous benefits to help. The members acknowledged that the existence of cooperatives was very helpful to support the business progress of entrepreneurs. With the existence of cooperatives, members can make loans in an easy way and cooperatives have different roles from other institutions because for various reasons, members above cooperative institutions are more in favor of entrepreneurs who have limited capital. The role of the "SURYA" UMG Savings and Loan Cooperative is very beneficial for micro and small entrepreneurs because with the amount of loans given to these entrepreneurs, these entrepreneurs try to take advantage of the loans provided by the cooperative